Management of Facilities and Infrastructure in Public Senior High School (SMAN) 71 Jakarta - Nadya Khairani Afiefa; Matin Matin; Heru Santosa (Eduvest - Journal of Universal Studies, 2024)
Management of educational facilities and infrastructure will have an impact on the optimal, effective, and efficient implementation of educational activities in schools. SMAN 71 Jakarta is known for its lush and comfortable environment, as well as adequate facilities and infrastructure to support the implementation of education in the school. Therefore, this research aims to determine how the management of educational facilities and infrastructure is conducted in SMAN 71 Jakarta. This study is a qualitative research using a descriptive approach. Data collection techniques in this research are conducted through observation, interviews, and documentation, known as data triangulation. Interviews were conducted with eight informants related to the management of educational facilities and infrastructure in the school. Furthermore, data analysis techniques in this research are carried out through three stages: data reduction, data presentation, and conclusion drawing. Based on the research results, it can be concluded that SMAN 71 Jakarta has implemented seven main functions of management of educational facilities and infrastructure, namely planning, procurement, distribution, inventory, maintenance, storage, and disposal, quite well although there are still some challenges in its implementation.